Why should anyone be led by you? : what it takes to be an authentic leader. - Goffee, Rob, ....-; Jones, Gareth R., 1951- (Boston : Harvard Business Review Press, 2006)
Too many companies are managed not by leaders, but by mere role players and faceless bureaucrats. What does it take to be a real leader--one who is confident in who she is and what she stands for and who truly inspires people to achieve extraordinary results? Rob Goffee and Gareth Jones argue that leaders don't become great by aspiring to a list of universal character traits. Rather, effective leaders are authentic: They deploy individual strengths to engage followers' hearts, minds, and souls. They are skillful at consistently being themselves, even as they alter their behaviors to respond effectively in changing contexts. In this lively and practical book, Goffee and Jones draw from extensive research to reveal how to hone and deploy one's unique leadership assets while managing the inherent tensions at the heart of successful leadership: showing emotion and withholding it, getting close to followers while keeping distance, and maintaining individuality while "conforming enough." Underscoring the social nature of leadership, the book also explores how leaders can remain attuned to the needs and expectations of followers. "Why Should Anyone Be Led by You?" changes forever how we view, develop, and practice the art of leadership, wherever we live and work.
Keywords: Leidinggeven